Using Scanning Electron Microscopy to Detect the Ultrastructural Variations in Eggshell Quality of Fayoumi and Dandarawi Chicken Breeds - Fathi, M.M.; El-Dein, A. Zein; El-Safty, S.A.; Radwan, Lamiaa M. (International Journal of Poultry Science, 2007)
An experiment was conducted to evaluate egg quality and ultrastructural measurements of eggshell in two Egyptian local breeds of chicken (Fayoumi and Dandarawi). A total of 162 females representing the two breeds were randomly assigned to the current experiment. They were housed in individual cages placed in an open-sided house under the same environmental, managerial and hygienic conditions. Maturation measurements including body weight and age at sexual maturity were determined. Also, egg production (number and weight) was recorded for the first 3 months of production cycle to calculate egg mass. To assess egg quality parameters (internal and external), a total of 90 eggs were randomly collected from each breed at 26 weeks of age. In addition, eggshell samples were prepared to investigate ultrastructural variations using scanning electron microscopy (SEM). The current results revealed that Fayoumi breed had a better performance at sexual maturity compared to Dandarawi one. Inferior egg production parameters during the first 3 months of laying cycle were associated with Dandarawi breed. With respect to internal egg quality, there were no significant differences between Fayoumi and Dandarawi breeds for liquid components as a percentage of egg weight. In addition, Haugh unit and yolk index as indicators to the quality of albumen and yolk, did not exhibit a difference between breeds. Regarding eggshell quality traits, it could be noticed that Fayoumi breed significantly increased specific gravity and eggshell strength compared to Dandarawi one. In terms of ultrastructural measurements of eggshell, SEM inspection revealed that eggshell of Fayoumi breed had a higher effective thickness (palisade layer) compared to Dandarawi one. On the other hand, the length of mammillary layer (absolute or relative) was significantly lower in eggshells of Fayoumi hens compared to those of Dandarawi counterparts. Type B bodies, which are rounded and located among mammillary caps, were more frequent in eggshell of Dandarawi breed resulting in poor shell quality. However, Fayoumi breed had good rounded caps and early fusion as compared to Dandarawi one. The incidence of mammillary alignment and erosion were more common in eggshell of Dandarawi breed suggesting poor shell strength. In conclusion, Fayoumi breed had genetically not only better egg production and egg quality but also good ultrastructural formation of eggshell compared to Dandarawi breed.